Early-stage findings in an experimental calf model infected with Argentinean isolates of Mycobacterium avium subsp. Paratuberculosis - Ingratta, Giselle Gabriela; Stempler, Ana; Fernández, Bárbara; Colavecchia, Silvia Beatriz; Jolly, Ana; Minatel, Leonardo; Paolicchi, Fernando; Mundo, Silvia Leonor (Elsevier, 2023)
Mycobacterium avium subsp. paratuberculosis (MAP) is an important pathogen that causes granulomatous enteritis known as Johne’s disease or paratuberculosis (PTB). In this study an experimental model of calves infected with Argentinean isolates of MAP for 180 days was used to provide more data of the early PTB stages. Calves were challenged by oral route with MAP strain IS900-RFLPA (MA; n = 3), MAP strain IS900-RFLPC (MC; n = 2) or mock infected (MI; n = 2), and response to infection was evaluated through peripheral cytokine expression, MAP tissue distribution and histopathological early-stage findings. Specific and varied levels of IFN-γ were only detected at 80 days post-infection in infected calves. These data indicate that specific IFN-γ is not a useful indicator for early detection of MAP infection in our calf model. At 110 days post-infection, TNF-α expression was higher than IL-10 in 4 of the 5 infected animals and a significant decrease of TNF-α expression was detected in infected vs. non-infected calves. All calves challenged were identified as infected by mesenteric lymph node tissue culture and real time IS900 PCR. In addition, for lymph nodes samples, the agreement between these techniques was almost perfect (κ = 0.86). Colonization of tissues and levels of tissue infection varied between individuals. Evidence of early MAP dissemination to extraintestinal tissues such as the liver was detected by culture in one animal (MAP strain IS900-RFLPA). In both groups microgranulomatous lesions were observed predominantly in the lymph nodes, with giant cells present only in the MA group. In summary, the findings described herein may indicate that local MAP strains induced specific immune responses with particularities that could suggest differences in their biological behavior. Further studies should be carried out in order to obtain an in-depth understanding of the influence of MAP strains in host-pathogen interactions and the outcome of disease.